Bigger is Better or how Governments Learned to Stop Worrying and Love Megaprojects - Menga, Filippo (Studies of Transition States and Societies, 2018)
Megaprojects, with their sheer size and their physical and emotional impact, can emerge as central elements around which political elites construct an ideology. Following a comparison of the narratives surrounding the Strait of Messina Bridge in Italy and the Rogun Dam in Tajikistan, I find that similar narratives appear in arguments for mega projects across different regime types, as advocates portray large infrastructure as a panacea for varied problems and thus justify the significant investment such projects require. Politicians in both Italy and Tajikistan have embraced images of heroic progress toward a better future to frame megaprojects as inevitable signs of progress and national well-being.